Голубой дым: повесть ; рассказы / Г. В. Семенов ; худож. Л. Ф. Шканов - Семенов Георгий Витальевич (Советская Россия, 1983)
Экземпляры: б/ф №1 (20200218) / Инвентарный номер: 4641 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 30 / ББК: 84(2Рос=Рус)6